The rich and the poor on the spectrum in 1 Timothy 6:17–19: A text-centred interpretation - Tsholofelo J. Kukuni (HTS Teologiese Studies/Theological Studies)
This article applies a novel rhetorical approach, ‘text-generated persuasion interpretation’ (TGPI), to 1 Timothy 6:17–19, exploring its relevance to South Africa, particularly the national poverty line (NPL). Rooted in South Africa’s socio-economic realities, the interpretation reflects the fluid nature of wealth and poverty, requiring regular updates to the NPL by Statistics South Africa (STATS SA) because of the evolving cost of living. This fluidity is also evident in the socio-economic context of ancient Ephesus, to which 1 Timothy 6:17 pertains. The directive to Timothy to ‘instruct those who are rich in this present world’ suggests that the categories of rich and poor are not fixed. The article challenges the view that the ‘rich’ form a distinct, hegemonic group, arguing that anyone with more than basic necessities (Tm 1 6:8) should be considered above the NPL. While the NPL is crucial for measuring welfare in South Africa, this study interprets the 1 Timothy 6:17–19 passage in the South African context, suggesting that wealth extends beyond traditional definitions and calls on individuals with surplus resources to contribute to social welfare, fostering a more inclusive understanding of wealth and stewardship.